Analysis of Factors Influencing Muslim Consumers’ Intention to Boycott Unilever Products Related to the Israel–Palestine Conflict (A Study on Generation Z Muslims in Semarang City) - Rahma Putri Allisa Wibowo; Ariza Fuadi (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the influence of attitude toward behavior, subjective norms, perceived behavioral control, and Fatwa MUI No. 83 of 2023 on the boycott intention of Generation Z Muslims in Semarang City toward Unilever products. Data were collected through an offline survey involving 110 respondents and analyzed using multiple linear regression. The results indicate that all four variables significantly affect the intention to boycott. This study also reinforces the validity of the TPB within the context of boycott behavior and provides practical implications for multinational companies, particularly Unilever, to be more responsive to social and religious issues in order to maintain consumer loyalty amid sensitive geopolitical circumstances.